Microtubules Regulate Migratory Polarity through Rho/ROCK Signaling in T Cells - Takesono, Aya (Public Library of Science, 2010)
BACKGROUND: Migrating leukocytes normally have a polarized morphology with an actin-rich lamellipodium at the front and a uropod at the rear. Microtubules (MTs) are required for persistent migration and chemotaxis, but how they affect cell polarity is not known. METHODOLOGY/PRINCIPAL FINDINGS: Here we report that T cells treated with nocodazole to disrupt MTs are unable to form a stable uropod or lamellipodium, and instead often move by membrane blebbing with reduced migratory persistence. However, uropod-localized receptors and ezrin/radixin/moesin proteins still cluster in nocodazole-treated cells, indicating that MTs are required specifically for uropod stability. Nocodazole stimulates RhoA activity, and inhibition of the RhoA target ROCK allows nocodazole-treated cells to re-establish lamellipodia and uropods and persistent migratory polarity. ROCK inhibition decreases nocodazole-induced membrane blebbing and stabilizes MTs. The myosin inhibitor blebbistatin also stabilizes MTs, indicating that RhoA/ROCK act through myosin II to destabilize MTs. CONCLUSIONS/SIGNIFICANCE: Our results indicate that RhoA/ROCK signaling normally contributes to migration by affecting both actomyosin contractility and MT stability. We propose that regulation of MT stability and RhoA/ROCK activity is a mechanism to alter T-cell migratory behavior from lamellipodium-based persistent migration to bleb-based migration with frequent turning.